La Lutte contre le racisme et la xénophobie. - Hanotiau, Michel; Batselé, Didier; Daurmont, Odile (Bruxelles : Editions Nemesis, 1992)
Fonds VCIM
Collection dirigée par Pierre Lambert
Préface de Philipppe Moureaux
Frans
Monografie